Bringing stroke clinical guidelines to life. Issue 4 (June 2019) - English, Coralie; Bayley, Mark; Hill, Kelvin; Langhorne, Peter; Molag, Marja; Ranta, Annemarei; Solomon, John M; Turner, Tari; Campbell, Bruce CV
Clinical practice guidelines are essential for driving evidence-based clinical care to patients. In an era of ever-increasing research evidence, keeping guidelines up to date is a challenging and resource-intensive process. Advances in technological platforms provide opportunities to develop new models of guideline development that will allow for continuous, rapid updates to recommendations as new evidence emerges. As Australia and other countries begin to develop these models, we have an opportunity to work more closely together to ensure the most efficient use of resources.